Constructive Nonsmooth Analysis and Related Topics - Demyanov, Vladimir F.; Pardalos, Panos M.; Batsyn, Mikhail; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This volume contains a collection of papers based on lectures and presentations delivered at the International Conference on Constructive Nonsmooth Analysis (CNSA) held in St. Petersburg (Russia) from June 18-23, 2012. This conference was organized to mark the 50th anniversary of the birth of nonsmooth analysis and nondifferentiable optimization and was dedicated to J.-J. Moreau and the late B.N. Pshenichnyi, A.M. Rubinov, and N.Z. Shor, whose contributions to NSA and NDO remain invaluable. The first four chapters of the book are devoted to the theory of nonsmooth analysis. Chapters 5-8 contain new results in nonsmooth mechanics and calculus of variations. Chapters 9-13 are related to nondifferentiable optimization, and the volume concludes with four chapters containing interesting and important historical chapters, including tributes to three giants of nonsmooth analysis, convexity, and optimization: Alexandr Alexandrov, Leonid Kantorovich, and Alex Rubinov. The last chapter provides an overview and important snapshots of the 50-year history of convex analysis and optimization.
Constructive Noonsmooth Analysis and Related Topics (V. Demyanov, P.M. Pardalos, M. Batsyn) -- Use Model Theory in Nonsmooth Analysis (S.S. Kutateladze) -- Demyanov Difference in Infinite Dimensional Spaces (J. Grzybowski, D. Pallaschke, R. Urbanski) -- Separable Reduction of Metric Regularity Properties (A.D. Ioffe) -- Construction of Pairs of Reproducing Kernel Banach Spaces (P.G. Georgiev, L. Sanchez-Gonzalez, P.M. Pardalos) -- On the Regularization Method in Nondifferentiable Optimization Applied to Hemivariational Inequalities (N. Ovcharova, J. Gwinner) -- Dynamics and Optimization of Multibody Systems in the Presence of Dry Friction (F.L. Chemousko) -- Method of Steepest Descent for Two-Dimensional Problems of Calculus in Variations (M.V. Dolgopolik, G.Sh.Tamasyan) -- On a Quantitative Semicontinuity Property of Variational Systems with Applications to Perturbed Quasidifferentiable Optimization (A. Uderzo) -- Some Remarks on Bi-Level Vector Extremum Problems (C. Antoni, F. Giannessi) -- Well-Posedness for Lexicographic Vector Equilibrium Problems (L.Q. Anh, T.Q. Duy, A.Y. Kruger, N.H. Thao) -- The Best Linear Separation of Two Sets (V.N. Malozemov, E.K. Cherneutsanu) -- Alternance Form of Optimality Conditions in the Finite-Dimensional Space (V.F. Demyanov, V.N. Malozemov) -- Optimal Multiple Decision Statistical Procedure for Inverse Covariance Matrix (A.P. Koldanov, P.A. Koldanov) -- Conciliating Generalized Derivatives (J.-P. Penot) -- The Nonsmooth Path of Alex M. Rubinov (S.S. Kutateladze) -- Two Giants From St. Petersburg (S.S. Kututeladze) -- Convex Analysis and Optimization in the Past 50 Years: Some Snapshots (J.-B. Hiriart-Urruty).
Keywords: Mathematics; Differentiable dynamical systems; Algorithms; Computer science; Mathematical optimization; Mathematics; Optimization; Algorithms; Dynamical Systems and Ergodic Theory; Computational Science and Engineering